Peningkatan Kemampuan Kerjasama melalui Metode Proyek pada Anak Usia 5-6 Tahun - Kusumawati, Nurjanah Indah; Nirmala, Ine; Syafrida, Rina (Absorbent Mind, 2024)
The ability to collaborate through the project method is one effort to stimulate learning that is done together. This research aims to improve cooperation skills through the project method in children aged 5-6 years in Ra Mathla'ul Anwar Telukambulu Karawang. In this writing, the author uses the Classroom Action Research (PTK) method which is carried out in 2 cycles. The results show that children's cooperation through this project method can improve well. It is known that in the pre-action period, children's cooperative abilities obtained an average value of 27.5%, then continued with action cycle I, which obtained an average value of 51.3%, showing improved results but not yet reaching the target and continued in cycle II which obtained the average value of 83.7% shows very good improvement results. Researchers assess that this research has achieved success because it has exceeded the predetermined limit of 75%.